" The Effect of the Auditor's Experience on the Quality of Internal Audit " - خضير, بشرى فاضل; عبد الرزاق, عمار لؤي (Journal of Economics and Administrative Sciences, 2017)
The importance of internal audit in the growing demand for services in the public and private economic units, and in the rapid growth of its systems professional, has also been recognition of the importance of internal audit quality and the quality of information provided in a long time, as well as the importance of achieving the greatest possible quality in his work to reduce accounting risks of financial reports misleading or fraudulent, which is one of the important features of the audit.The internal audit quality are linked with the ability of auditors to detect errors in the financial statements, and their willingness to express an opinion technical neutral and non-aligned based on the results of the audit process, improve efficiency and organizational effectiveness of economic units through the constructive criticism, and in fact the internal audit has become an indispensable tool for achieving effective control in economic units. Also internal audit quality will increase the adoption of external audit on the work of the internal audit, which increases the efficiency of the external audit and reduce its burden.As the experience in the work ensures achievement of the objectives, the internal audit experience plays an important role in ensuring achievement of its economic units objectives and objectively.In this research will be to examine the impact of Internal Auditors experience of scientific and practical point of view on the quality of internal audit work, depending on the survey method through knowledge of the opinions of a sample of auditors working in the departments of control and internal audit in the Ministry of Higher Education and Scientific Research, and the University of Baghdad and Nahrain University and the Post Graduate Institute for Accounting & Financial Studies, and analysis data using the statistical analysis system (SAS).